GEDUNG OLAHRAGA KABUPATEN KETAPANG - Rudianto, Eko Wibowo; Putro, Jawas Dwijo; Khaliesh, Hamdil (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Ketapang is a district-level area that is constantly developing and trying to improve the welfare of the community. One of these efforts is the development process in various sectors. In line with the growth and development of the development process in these various sectors, the development that is felt to need attention at this time in Ketapang Regency is development in the field of sports. The importance of developing the sports sector in society. Ketapang Regency is based on the level of public awareness of the importance of exercise which is increasing day by day, in line with the recommendations of health experts. This final project aims to design sports facilities that are not only functional but also multifunctional. The Ketapang Regency Sports Building design method is carried out in several stages, namely ideas, theory reviews, data collection, analysis, synthesis, pre-design, and design. The design analysis resulted in several functions of the sports building into three functions, namely primary functions (sports and competitions), secondary functions (administration and recreation), and tertiary functions (maintenance/service). The analysis of the area pattern is taken from the elements of the formation of the sports building area in general by adjusting the location of the site. The characteristics of the sports building follow the shape of the sports building by using a wide span structure with a spaceframe roof system.